Increased Knowledge of Literacy of Latin Letters and Reading the Qur'an of Housewives in Barru Regency - Supriadi; A. Pananrangi M; Musbaing (Medan Resource Center, 2022)
Some of the partner problems that are the focus of PKM activities are among others; The existence of limitations in reading and writing Latin letters in this case IRT is illiterate. The second problem is the lack of knowledge of Reading the text of the Qur'an. The existence of this problem, the solution offered in this PKM activity is: increasing the knowledge of literacy of Latin letters of Housewives in Barru Regency. increase knowledge about reading the text of the Quranic scriptures, increase the ability to think in IRT in Barru Regency, increase knowledge in science and technology and art at IRT in Barru Regency, increase knowledge of religion at IRT in Siawung Village, Barru Regency, Increase knowledge about the importance of innovation in IRT in Barru Regency. The solution that occurs can be eliminated through IRT training and assistance activities in Barru Regency through activities to increase knowledge of Latin letter literacy and Quranic literacy, the focus of this activity is focused on Siawung Village, Barru Regency, Barru District, Barru Regency. The method used is the participatory method. This method is implemented by involving all members of partner groups, village governments, and the relevant local governments and several community leaders. It is hoped that they will be able to read and write the Quran, so that the IRT in Barru Regency can understand the reading of the Quran. The results of this PKM show that the increase in knowledge of reading Latin letters and the Quran in IRT in Barru Regency through PKM activities has given understanding to IRT in Barru Regency. IRT has been able to recognize letters, recognize syllables, recognize words, and recognize sentences. IRT has been able to write identities, so pkm activities carried out in Barru Regency have succeeded in increasing knowledge of literacy of Latin letters and the Quran.